Pemahaman dan Penerimaan Label Gizi Front of Pack Produk Snack oleh Siswa SMA di Depok - Iftita Rakhma Ikrima; Puspo Edi Giriwono; Winiati Pudji Rahayu (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2023)
Labels play a crucial role in providing essential information that helps consumers choose their food products. Despite this, the comprehension and acceptance of nutrition labels remain low. The objective of this study was to compare the understanding and acceptance of nutrition labels with and without Front of Pack (FoP) in adolescents aged between 15 and 18 years. The FoP nutrition label is a labeling system that simplifies nutritional information and displays it on the front of food packaging. It includes three types: daily intake guide (DIG), multi-traffic light (MTL), and health star rating (HSR). The study targeted high school students in Depok, selected through stratified sampling based on school accreditation. Only 11.1% of respondents reported reading nutrition labels. The results of the Chi-square test indicated a significant difference (p <0.05) in the use of nutrition labels based on exposure to nutrition, nutritional knowledge, and label reading. ANOVA test results showed significant differences in comprehension and acceptance of the four labels. The HSR label was the most comprehensible (63.7%), followed by DIG (58.7%), nutrition fact panel/NFP (51.1%), and MTL (45.7%). Additionally, respondents rated the HSR label as the most preferred, attractive, and easiest to understand.